Narcotic Drugs as Objects of Forensic Investigation: Trends in the Context of the War in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2025)
Amidst large-scale Russian aggression against Ukraine, there has been a steady trend towards an increase in drug-related crime, particularly due to the illegal manufacture and sale of narcotic drugs and psychotropic substances. There has been a gradual transformation in the types of drugs seized from illegal circulation. Cannabis remains the most common substance in the group of narcotic drugs. On the other hand, the volume of cocaine and heroin seizures and forensic examinations has decreased significantly, as has the amount of poppy straw and acetylated opium. At the same time, the number of detections of tramadol and other potent medicines has increased. Among psychotropic substances, the number of detected samples of LSD and synthetic cannabinoids is decreasing, while the frequency of detection of amphetamine, methamphetamine, and especially synthetic cathinones, the largest share of which is α-pyrrolidinopentiophenone, is increasing. It is evident that the war has led to a reconfiguration of the routes for the illicit trafficking of heroin and cocaine outside Ukraine. The demand for narcotics is mainly met by domestic production of cannabis, amphetamine, methamphetamine, synthetic cathinones, as well as abuse of pharmaceutical drugs (methadone, tramadol, etc.).The priorities of law enforcement agencies are gradually shifting from focusing on minor arrests to identifying drug laboratories, drug dens and distribution channels, which can generally be seen as a positive trend.It is likely that under martial law and after the end of hostilities, domestic demand for drugs will continue to grow, particularly among people who need treatment for post-traumatic stress disorder and pain syndrome, or as a result of addiction developed during the war. Given the low income levels of the population, demand will focus on cheap synthetic drugs. To minimise harm in such a situation, it is advisable to ensure orderly and controlled access for patients to potent drugs, develop substitution maintenance therapy programmes, legalise medical cannabis, and develop a rehabilitation system for military personnel returning to civilian life.